Light-Based Therapies for Skin of Color - Baron, Elma.; SpringerLink (Online service) (London : Springer London, 2009)
The science and practice of photodermatology has been largely based on knowledge derived from white skin. Therapeutic modalities based on lasers and light sources are often based on protocols that have been utilized in Caucasian populations. The biologic effects of light in pigmented skin are not as well understood. Consequently, the mechanisms are only now being discovered and elucidated in darker skin types and therefore treatment strategies are now being developed that are more specifically tailored to these patients. Light Therapies for Skin of Color has been written to address the fact that there is little information in the literature providing suitable recommendations for treating pigmented skin with lasers and light sources. The information presented here represents current knowledge and the future directions. Included within are the basic foundations in photobiology, such as principles of optics, biology of photodamage and photoaging, protection afforded by endogenous pigmentation, and the issues surrounding the use of photoprotective agents in non-white skin. Practical information on the use of specific treatment modalities and the approach to specific dermatologic conditions in dark-skinned patients, such as vitiligo, follicular disorders, pigmentation, among others, are also included, making this book enormously useful to all dermatologists and other health care providers who manage patients with pigmented skin.
Principles of Light-Skin Interactions -- Photoaging in Skin of Color -- Endogenous Protection by Melanin -- Photoprotection in Non-Caucasian Skin -- Light Treatment of Follicular Disorders in Dark Skin -- Phototherapy for Vitiligo -- Lasers and Light Therapies for Pigmentation -- Light Therapies for Cutaneous T-Cell Lymphoma -- Light Treatment and Photodynamic Therapy in Acne Patients with Pigmented Skin -- Clinical Application of Intense Pulsed Light in Asian Patients.
Keywords: Medicine; Dermatology; Surgery; Plastic surgery; Medicine & Public Health; Dermatology; Plastic Surgery; Surgery; Electronic books